Reduced 25‐hydroxyvitamin D and risk of Alzheimer's disease and vascular dementia. Issue 3 (22nd July 2013) - Afzal, Shoaib; Bojesen, Stig E.; Nordestgaard, B⊘rge G.
Abstract: Background: Vitamin D deficiency has been implicated as a risk factor for dementia in several cross‐sectional studies. We tested the hypothesis that reduced plasma 25‐hydroxyvitamin D (25[OH]D) is associated with increased risk of Alzheimer's disease (AD) and vascular dementia in the general population. Methods: We measured baseline plasma 25(OH)D in 10, 186 white individuals from the Danish general population. Results: During 30 years of follow‐up, 418 participants developed AD and 92 developed vascular dementia. Multivariable adjusted hazard ratios for AD were 1.25 (95% confidence interval [CI], 0.95–1.64) for 25(OH)D less than 25 nmol/L vs. greater than or equal to 50 nmol/L, and 1.29 (95% CI, 1.01–1.66) for less than the 25th seasonally adjusted 25(OH)D percentile vs. more than the 50th seasonally adjusted 25(OH)D percentile. Multivariable adjusted hazard ratios for vascular dementia were 1.22 (95% CI, 0.77–1.91) for 25(OH)D less than 50 nmol/L vs. greater than or equal to 50 nmol/L, and 1.22 (95% CI, 0.79–1.87) for less than or equal to the 50th vs. more than the 50th seasonally adjusted 25(OH)D percentile. Last, multivariable adjusted hazard ratios for the combined end point were 1.28 (95% CI, 1.00–1.64) for 25(OH)D less than 25 nmol/L vs. greater than or equal to 50 nmol/L, and 1.27 (95% CI, 1.01–1.60) for less than the 25th vs. more than the 50th seasonally adjusted 25(OH)D. Conclusions: We observed an association of reduced plasma 25(OH)D with increased risk of the combined end point of AD and vascular dementia in this prospective cohort study of the general population.